Parliamentary System of Governance in Hungary According to the Constitution of October 18, 1989 - Brodziński, Witold (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
In October 1989 Hungary became a Republic with the President at the helm. The Council of Ministers was replaced by a Government with Prime Minister as its head. It is allowed that ministers without portfolio participate in the work of the Government alongside those that are heads of particular Ministries. The new system of the posts of the state secretary was created, in order to adjust the structure to the requirements of the coalition governments. The parliamentary system of governance has emerged as an outcome of political agreements in the period of 1989–1990 – during the so-called negotiated revolution. Its starting point was the meeting of the socalled „triangular table” with the participation of the government, the „satellite” actors and the anti-Communist opposition that took place in September 1989. The Hungarian Constitution amended in the Summer 1990 had unequivocally accepted the parliamentary system of governance. Similarly to the German Chancellor system, Hungarian form of parliamentarism is characterized by a relatively strong position of the head of government. In the opinion of some Hungarian constitutional experts the crux of the accepted political formula can be summarized in the following expression: „weak President of the Republic, relatively strong government and strong Parliament”. In the debate in June 1990 the Parliament had opted for a system of governance in which the Paliament – as chosen by the people – should remain the strongest political actor. The above remarks on the system of governance in Hungary after 1989 I treat as a fragmentary contribution to a discussion concerning the changes in the parliamentary system of governance in general. The system of governance has always undergone dynamic changes in the course of history. Hungarian constitutionalists have recently began the process of analysis of the phenomenon of the so-called presidentializing of the executive power in Hungary. To simplify the matter a bit, it can be said that the aforementioned notion is being understood as reinforcing of the office of the Prime Minister. Somehow against the intentions of the fathers of the Consitution of 1989, the Prime Minister assumes a peculiar role of a „national center”.